Penguatan Materi Hukum Bagi Guru Mata Pelajaran PPKn SMA Di Kabupaten Sragen - Widya Noventari noventari; Yudi Ariana; Triyanto; Rima Vien Permata Hartanto; Hassan Suryono; Triana Rejekiningsih; Dewi Gunawati (Jurnal Pengabdian UntukMu NegeRI, 2021)
Civic education contains material on law and politics. However, the fact have shown there are constraints faced by the teachers’ during the learning process due to the lack of knowledge, mastery, and understanding materials, especially regarding to the law material. Therefore, reinforcement at law material to civic education teacher is needed to support the learning process and achievement of civic education goals. As an effort to reinforcement law materials mastery and understanding, Law and Citizenship Research Group, Teacher Training and Education, Sebelas Maret University and MGMP PPKn, Sragen Regency, collaborated on mentoring civic education teachers through a community service program. The aims of this community service program are to: 1) enhance the knowledge, mastery, and understanding civic education teachers in law materials, 2) reinforce civic education teachers’ capacity to be a professional teacher. The benefit of this community service program is the sustainability of the Tri Dharma Perguruan Tinggi, i.e. education, research, and community service program. The final results of this program is produce professional civic education teachers’ accordingly professional teachers’ competence based on the regulation about the Role of teacher and Lecturer (Undang-Undang No 14 Tahun) in 2005